Performance of clostridium species and autochthonous bacteria from citrus wastewater under different carbon sources to produce biofuels - Camila da Silva, Daiana [UNESP]; Rodrigues, Caroline Varella; Canaver Marin, Danieli Fernanda [UNESP]; Lazaro, Carolina Zampol; Jacobus, Ana Paula [UNESP]; Pires, Lorena Oliveira [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Elsevier, 2024)
This study evaluated the energy recovery of citrus wastes with pure cultures (Clostridium acetobutylicum ATCC 824, Clostridium beijerinckii ATCC 10132 – Inocula 1 and 2, respectively) and an autochthonous microbial (Inoculum 3) from citrus wastewater (CW) in anaerobic batch reactors to produce biofuels (H2 and ethanol) fed with different carbon sources (glucose, maltose, fructose, sucrose, xylose, lactose, starch, acetate, and glycerol) in addition to CW. 4 conditions are tested: 1st - Inoculum 3, composed by Bacillus (20.44%), Clostridium (13.65%) and Lactobacillus (10.61%) was able to produce H2 with sucrose, glucose and fructose. 2nd - The highest metabolites were produced with TYA medium with Inocula 1 (374 mg L−1 of acetic acid) and 2 (611 mg L−1 of butanol). Inoculum 3 generated the highest ethanol (1571.8 mg L−1) in PYG medium. 3rd - In the same nutritional conditions (PYG), Inocula 1 and 2 produced H2 (36.80 and 64.10 mmol L−1, respectively) and acetic acid (246 and 201 mg L−1, respectively); the H2 was suppressed with inoculum 3 due to Lactobacillus genus. 4th H2 production was favored by autochthonous bacteria in CW. This study valued the autochthonous microorganisms in the possibility of bioconversion of organic matter into value-added products in addition to contribute to an environment-sustainable solution for citrus processing.
Keywords: Citrus wastes; Fermentation; H2; Mixed culture; Pure culture